Reducing inappropriate antibiotic prescribing for children in primary care: a cluster randomised controlled trial of two interventions - Lemiengre, M; Verbakel, J; Colman, R; De Burghgraeve, T; Buntinx, F; Aertgeerts, B; De Baets, F; De Sutter, A (Royal College of General Practitioners, 2018)
Background: Antibiotics are overprescribed for non-severe acute infections in children in primary care. Aim: To explore two different interventions that may reduce inappropriate antibiotic prescribing for non-severe acute infections. Design and setting: A cluster randomised, factorial controlled trial in primary care, in Flanders, Belgium. Method: Family physicians (FPs) enrolled children with non-severe acute infections into this study. The participants were allocated to one of four intervention groups according to whether the FPs performed: (1) a point-of-care C-reactive protein test (POC CRP); (2) a brief intervention to elicit parental concern combined with safety net advice (BISNA); (3) both POC CRP and BISNA; or (4) usual care (UC). Guidance on the interpretation of CRP was not provided. The main outcome was the immediate antibiotic prescribing rate. A mixed logistic regression was performed to analyse the data. Results: In this study 2227 non-severe acute infections in children were registered by 131 FPs. In comparison with UC, POC CRP did not influence antibiotic prescribing, (adjusted odds ratio [AOR] 1.01, 95% confidence interval [CI] = 0.57 to 1.79). BISNA increased antibiotic prescribing (AOR 2.04, 95% CI = 1.19 to 3.50). In combination with POC CRP, this increase disappeared. Conclusion: Systematic POC CRP testing without guidance is not an effective strategy to reduce antibiotic prescribing for non-severe acute infections in children in primary care. Eliciting parental concern and providing a safety net without POC CRP testing conversely increased antibiotic prescribing. FPs possibly need more training in handling parental concern without inappropriately prescribing antibiotics.